Intensive polyculture of common carp (Cyprinus carpio), mirror carp (Cyprinus carpio carpio), silver carp (Hypophthalmichthys Molitrix) and grass carp (Ctenopharyngodon Idella) at different stocking densities (Bangladesh Journal of Zoology, 2018)
An experiment was carried out for 6 months on rearing of common carp, mirror carp, grass carp and silver carp under polyculture system at different stocking densities in cemented tanks (5 - 7 m in diameter and water depth 1.0 - 1.5 m). Observations were made on fish growth in terms of monthly and per day weight gain. Grass carp attained the maximum weight 686 ± 17, 720 ± 16.5 and 765 ± 9.6 in three tanks, respectively. Weight gained followed by silver carp as 680 ± 10 g, 680 ± 12.6 g and 701 ± 9.2 g in tank 1, tank 2 and tank 3, respectively. The common carp gained its average maximum weight 525 ± 10.7 g in tank3 and the mirror carp also attained its maximum weight 500 ± 12.2 g in same tank. In common carp the maximum average daily weight gain (3.2 ± 0.1 g) was in the month of December and lowest was (1.92 ± 0.2 g) in the month of August in tank 3. In mirror carp the maximum average daily weight gain (3.03 ± 0.09 g) was in the month of September and lowest (1.41 ± 0.07g) in the month of July in tank 3 and tank 2, respectively. In grass carp the maximum average daily weight gain (4.24 ± 0.17 g) was in the month of August and lowest (2.72 ± 0.07 g) in the month of July in tank 3 and tank 1, respectively. Among silver carp the maximum average daily weight gain (4.45 ± 0.01 g) recorded in the month of October and lowest was (2.61 ± 0.11 g) in the month of July in tank 1. The specific growth rate (SGR) was 1.23 ± 0.64 to 1.33 ± 0.83 in common carp, 1.27 ± 0.9 to 1.34 ± 0.8 in mirror carp, 1.36 ± 0.86 to 1.55 ± 1.13 in grass carp and 1.41 ± 0.83 to 1.52 ± 1.09 in silver carp in different culture treatments.Bangladesh J. Zool. 46(1): 71-80, 2018